If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 6v = 72 Solving 6 + 6v = 72 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6v = 72 + -6 Combine like terms: 6 + -6 = 0 0 + 6v = 72 + -6 6v = 72 + -6 Combine like terms: 72 + -6 = 66 6v = 66 Divide each side by '6'. v = 11 Simplifying v = 11
| 8(-7)-5y=-6 | | 4(s+5)=28 | | 21=12+b | | Y=4x^2+8x-1 | | -3x-6=-30-x | | 11600/4 | | 6x+18=2x-32 | | W+1=2 | | (x+2)2+(y-12)2=36 | | 15x-10y=20 | | 2.5x^2-8*x=20 | | -6n+(-12)+4n= | | Log(x+2)+log(x-1)= | | 6+6r=12 | | 7/(x-8)=3/x | | 3x-8=-4x-92 | | 50x=80x | | 15=46-(2y+1) | | (4-1/3x)^3 | | 64-16y+2y^2=32 | | 4w+14=46 | | X^2+y^2+41=0 | | og(x+2)+log(x-1)=1 | | 3/5x1/5 | | 4x(3+8)-7= | | -7y-24=-8-9 | | 2x-(3-7x)+4(3-x)=7x-3(x-1) | | 4w-4x-y+3w+18x-8y= | | 2x+8=3-2x | | 1=9-3 | | T-(x-8)=-2 | | 18P-226=48 |